A high-conductivity corrosion-resistant epoxy resin-based protective coating for titanium electrode plates, a preparation method and applications thereof

CN122917628APending Publication Date: 2026-10-16CHANGZHOU XIYAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610987932.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]现有技术中存在的问题是:PEM电解槽阳极使用的以过渡金属化合物涂层为保护涂层的常规钛电极耐腐蚀性不佳,析氧过电位较大

Benefits of technology

(1)本发明以环氧树脂作为成膜物,配合潜伏性环氧固化剂使用,能够在钛基体表面形成一层致密且附着力良好的保护涂层。该涂层在PEM电解槽阳极强酸性、高电位的析氧环境中能够有效阻隔电解液与钛基体的直接接触,从而显著延缓钛基体表面钝化膜的形成,降低界面接触电阻的上升速率,延长电极在电解工况下的有效使用寿命。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of hydrogen production by electrolysis of water, and particularly relates to a high-conductivity corrosion-resistant epoxy resin-based protective coating for titanium electrode plates, a preparation method and application thereof. The conventional titanium electrode used in the anode of a PEM electrolytic cell has poor corrosion resistance and a large oxygen evolution overpotential, and uses a transition metal compound coating as a protective coating. In view of the above problems, the present application provides a high-conductivity corrosion-resistant epoxy resin-based protective coating for titanium electrode plates. The coating comprises epoxy resin, latent epoxy curing agent, silane coupling agent, epoxy toughening agent, sodium-based montmorillonite, flaky talc powder and conductive dispersion liquid. The present application uses a composite conductive agent to construct a continuous conductive network in the coating, and simultaneously uses the swelling and peeling characteristics of sodium-based montmorillonite in water and the hydrophobic filling effect of talc powder to form a synergistic barrier effect, so that the coating has excellent conductivity and acid electrolyte corrosion resistance, and can replace the noble metal oxide coating for titanium electrode protection in a PEM electrolytic cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water electrolysis for hydrogen production technology, specifically to a highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates, its preparation method, and its application. Background Technology

[0002] Hydrogen production through water electrolysis is widely regarded as a key technological pathway to achieving dual-carbon goals and building a clean energy system. With the recent flurry of hydrogen energy-related policies in my country, the green hydrogen industry is experiencing rapid development. Among water electrolysis technologies, proton exchange membrane (PEM) electrolyzers have attracted significant attention due to their advantages such as high current density, fast response speed, and adaptability to fluctuations in renewable energy. One of the core components of an electrolyzer is the electrode, whose performance directly affects hydrogen production efficiency, energy consumption, and equipment lifespan.

[0003] Titanium, with its excellent mechanical strength, good corrosion resistance, and low density, is an ideal substrate material for manufacturing electrodes for PEM electrolyzers, especially the porous transport layer and bipolar plates on the anode side. However, under the operating conditions of the PEM electrolyzer anode, the high anodic potential and strongly acidic environment (local pH can be below 1) cause a non-conductive titanium dioxide passivation film to rapidly form on the titanium substrate surface. This passivation film significantly increases the interfacial contact resistance, leading to a sharp increase in the cell voltage and ultimately causing the entire electrolyzer to fail. Therefore, preparing a protective coating on the titanium substrate surface that combines high conductivity, high adhesion, resistance to electrolyte corrosion, and long-term stability is a core problem that needs to be solved in titanium electrode technology.

[0004] Currently, the mainstream technical solution for protective coatings on titanium electrodes is noble metal or mixed metal oxide coatings. These electrodes typically use titanium as the substrate, coated with active coatings of noble metal oxides such as iridium or ruthenium. Representative preparation processes include thermal decomposition (coating a noble metal salt solution onto a titanium substrate followed by high-temperature sintering), sol-gel methods, and physical vapor deposition methods such as magnetron sputtering. These coatings can protect the titanium substrate while exhibiting electrocatalytic activity, demonstrating superior chemical stability and corrosion resistance, and the related processes are relatively mature. However, the main limiting factor for this approach is the scarcity and high cost of noble metal resources, which is also the main bottleneck restricting its large-scale application.

[0005] To reduce material costs, transition metal compound coatings, mainly including transition metal nitrides and phosphides, have become a research hotspot in recent years. These coatings hold promise for replacing some precious metal materials, thereby significantly reducing electrode manufacturing costs. However, these coatings still face several technical challenges: their conductivity is often inferior to that of precious metal oxide coatings; their corrosion resistance is insufficient in strongly acidic, high-potential oxygen evolution environments, resulting in a shorter service life; furthermore, the adhesion between the coating and the titanium substrate is poor, making it prone to oxidation and peeling during long-term operation. Summary of the Invention

[0006] A problem with existing technologies is that conventional titanium electrodes used as anodes in PEM electrolytic cells, with transition metal compound coatings as protective coatings, exhibit poor corrosion resistance and a large oxygen evolution overpotential. To address these issues, this invention provides a highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates. The coating has a particle size ≤5μm and its formulation includes epoxy resin, a latent epoxy curing agent, a silane coupling agent, an epoxy toughening agent, montmorillonite, talc, and a conductive dispersion. The mass ratio of latent epoxy curing agent to epoxy resin, based on solids, is 1:(9-10). The total mass of latent epoxy curing agent and epoxy resin, based on solids, is denoted as epoxy resin matrix; The mass addition amount of silane coupling agent is 1-3% of the mass of epoxy resin matrix; The amount of epoxy toughening agent added is 7-10% of the mass of the epoxy resin matrix; The mass addition amount of montmorillonite is 1-3% of the mass of the epoxy resin matrix; The amount of talc added is 2-4% of the mass of the epoxy resin matrix; The mass addition of the conductive dispersion does not exceed 50% of the mass of the epoxy resin matrix, the solid content of the conductive dispersion is 15-17%, the conductive agent in the conductive dispersion is composed of Ketjen black, graphene and carbon nanotubes in a mass ratio of 4:4:2, and the particle size of the conductive dispersion is ≤1μm.

[0007] Preferably, the epoxy resin is E51 epoxy resin.

[0008] Preferably, the silane coupling agent is KH550 or KH560.

[0009] Preferably, the montmorillonite is sodium-based montmorillonite.

[0010] Preferably, the talc is in the form of flakes.

[0011] Preferably, the graphene is of type HG1004 and was purchased from Henan Huage Graphene Materials Co., Ltd.

[0012] Preferably, the carbon nanotubes are of the GP1001M type and were purchased from LG Chem in South Korea.

[0013] Preferably, the Ketjen Black model is 600JD, purchased from Lion Corporation of Japan.

[0014] Preferably, the epoxy toughening agent is model 9301 toughening agent, purchased from Guangzhou Shanghe New Material Technology Co., Ltd.

[0015] Preferably, the latent curing agent is HS-601 liquid latent curing agent, purchased from Chuzhou Huisheng Electronic Materials Co., Ltd.

[0016] Beneficial effects: (1) This invention uses epoxy resin as the film-forming agent, in conjunction with a latent epoxy curing agent, to form a dense and well-adhesive protective coating on the surface of a titanium substrate. This coating effectively blocks direct contact between the electrolyte and the titanium substrate in the strongly acidic, high-potential oxygen evolution environment of the PEM electrolytic cell anode, thereby significantly delaying the formation of a passivation film on the titanium substrate surface, reducing the rate of increase in interfacial contact resistance, and extending the effective service life of the electrode under electrolytic conditions.

[0017] (2) This invention incorporates a composite conductive agent composed of Ketjen black, graphene, and carbon nanotubes in a mass ratio of 4:4:2 into an epoxy resin matrix, controlling the amount added to not exceed 50% of the epoxy resin matrix mass. Simultaneously, the solid content of the conductive dispersion is 15-17%. Through the synergistic effect of these components, a continuous and efficient conductive network can be constructed within the coating. This conductive network ensures excellent electronic conductivity of the coating, with an overall volume resistivity below 0.02 Ω·cm, enabling uniform current conduction on the titanium electrode surface and meeting the conductivity requirements of the water electrolysis process. When the titanium electrode using this coating is used as the anode in a PEM electrolyzer, its oxygen evolution overpotential is significantly lower than that of titanium electrodes using conventional transition metal compound coatings. Under long-term electrolysis operation conditions, the coating resistance change rate is low, thereby reducing additional energy consumption during electrolysis and contributing to improved overall energy efficiency of the electrolyzer.

[0018] (3) This invention enhances the interfacial bonding strength between the coating and the titanium substrate by adding a silane coupling agent to chemically bridge the interface between the titanium substrate and the organic coating. Simultaneously, the epoxy toughening agent improves the toughness of the cured epoxy resin, effectively mitigating the tendency of the coating to develop microcracks under thermal and mechanical stress. These combined effects improve the structural stability of the coating under bubble erosion and electric field aging conditions, reducing the risk of peeling and detachment during long-term operation, and ensuring that the electrode maintains good protective performance under electrolytic cell start-up and shutdown and load fluctuation conditions.

[0019] (4) This invention introduces sodium montmorillonite and talc as functional fillers into the coating formulation. Sodium montmorillonite has a typical 2:1 layered silicate structure with high viscosity and thixotropy. Its interlayer contains exchangeable sodium ions and water molecules. Upon contact with water, the interlayer distance increases, allowing it to expand significantly (up to 20-30 times) and form a thixotropic gel structure. During the coating curing process, this expansion characteristic of sodium montmorillonite helps its layers fully peel and align within the coating, forming a dense physical barrier network and effectively extending the penetration path of corrosive media. Talc has a dense structure and a hydrophobic surface, lacking expansion properties. Its flake-like particles can fill the micro-regions between the montmorillonite flake networks, further improving the coating's density and impermeability. The two types of lamellar fillers complement each other in terms of expandability and hydrophobicity: the expandable exfoliation of montmorillonite forms the basic barrier framework for the coating, while the hydrophobic filling of talc seals the weak areas in the framework. Their synergistic effect creates a complete labyrinthine barrier effect within the coating, effectively blocking the penetration of oxygen, electrolyte, and ions, significantly improving the long-term corrosion resistance of the coating in acidic electrolytes, and effectively inhibiting electrochemical erosion and pitting corrosion of titanium electrode plates during water electrolysis. Furthermore, sodium-based montmorillonite possesses a huge specific surface area (up to 240 m²). 2 / g) helps to enhance the interaction between molecules inside the coating and improve the cohesive strength of the coating; while the high true density and small specific surface area of ​​talc help to reduce the porosity of the coating. The difference between the two in structural characteristics complements each other, which further optimizes the overall density of the coating.

[0020] (5) The coating provided by the present invention is a liquid coating that can be applied to the surface of titanium electrode plates by conventional coating methods such as spraying, brushing or roller coating. It does not require expensive vacuum coating or high-temperature sintering equipment, the process is simple, it is highly adaptable to the shape of the substrate, and it is easy to achieve uniform coating of large-area electrode plates. This helps to reduce the cost of protective treatment of titanium electrodes and promotes the large-scale application of high-performance and low-cost titanium electrodes in PEM electrolytic cells.

[0021] (6) This invention replaces traditional precious metal oxide coatings and some transition metal compound coatings with an organic coating system, significantly reducing reliance on scarce precious metal resources such as iridium and ruthenium. Raw materials are widely available and costs are controllable. Simultaneously, the coating preparation process eliminates the need for high-temperature sintering, significantly reducing energy consumption and meeting the green hydrogen industry's requirement for low-carbon development across the entire chain, demonstrating good economic and environmental friendliness. Furthermore, the composite filler synergistically optimizes the system's conductivity, reducing the amount of high-end conductive fillers and precious metals while ensuring the coating's conductivity and protective properties, further lowering production costs and making it suitable for industrial application. Detailed Implementation

[0022] The present invention will be described in detail below with reference to embodiments. However, it should be understood that the following embodiments are merely illustrative examples of implementation of the present invention and are not intended to limit the scope of the present invention.

[0023] Example 1 A highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates is uniformly mixed with epoxy resin, latent epoxy curing agent, silane coupling agent, epoxy toughening agent, montmorillonite, talc powder and conductive dispersion. The epoxy resin is E51 epoxy resin, specifically Phoenix brand E51, purchased from Baling Petrochemical.

[0024] Montmorillonite is sodium-based montmorillonite, product number: M916670, model: sodium-based montmorillonite K-10, with a specific surface area of ​​240 m². 2 / g, purchased from Shanghai McLean Biochemical Technology Co., Ltd.

[0025] The talc powder is in flake form, model number T928098, and was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0026] The epoxy toughening agent, model 9301, was purchased from Guangzhou Shanghe New Material Technology Co., Ltd.

[0027] The latent epoxy curing agent, model HS-601 liquid latent curing agent, was purchased from Chuzhou Huisheng Electronic Materials Co., Ltd.

[0028] The dispersant used was LD1126 dispersant from Anhui Jiazhi Xinno Chemical Co., Ltd.

[0029] The total mass of latent epoxy curing agent and epoxy resin, based on solids, is denoted as epoxy resin matrix; The mass ratio of latent epoxy curing agent to epoxy resin is 1:10 based on solids content. The mass addition amount of the silane coupling agent is 2% of the mass of the epoxy resin matrix; The amount of epoxy toughening agent added is 8% of the mass of the epoxy resin matrix; The mass addition amount of montmorillonite is 2% of the mass of the epoxy resin matrix; The amount of talc added is 3% of the mass of the epoxy resin matrix; The conductive dispersion was added at 50% of the epoxy resin matrix by mass, and its solid content was 16%. The conductive agent in the dispersion consisted of Ketjen Black, graphene, and carbon nanotubes in a mass ratio of 4:4:2. The particle size of the conductive dispersion was ≤1μm. The graphene was HG1004, purchased from Henan Huage Graphene Materials Co., Ltd.

[0030] The carbon nanotubes, model GP1001M, were purchased from LG Chem in South Korea.

[0031] The Ketjen Black model is 600JD, purchased from Lion Corporation of Japan.

[0032] The coating formulation is as follows: 91g of E51 epoxy resin, 18.2g of latent epoxy curing agent, 2g of silane coupling agent KH560, 8g of epoxy toughening agent, 2g of sodium montmorillonite, 3g of talc, and 1000g of conductive dispersion.

[0033] The preparation method of the conductive dispersion is as follows: Dispersant LD1126 was added to solvent NMP and stirred until homogeneous. Then, carbon nanotubes, Ketjen black, and graphene powder were added and stirred until homogeneous. The mixture was then transferred to a sand mill for sand milling. The sand milling process parameters were: rotation speed 2500 rpm, time 2 h, cooling circulating water temperature controlled below 10℃ during sand milling, and sand milling was stopped when the particle size of the dispersion was 1 μm to obtain a conductive dispersion. The mass percentages of dispersant LD1126, Ketjen black, graphene powder, and carbon nanotubes in the conductive dispersion were 6%, 4%, 4%, and 2%, respectively.

[0034] The preparation method of the highly conductive and corrosion-resistant epoxy resin-based protective coating for the titanium electrode plate is as follows: According to the formula, the conductive dispersion is mixed evenly with epoxy resin, latent epoxy curing agent, silane coupling agent, epoxy toughening agent, montmorillonite, and talc. Then, it is ground using a three-roll mill in the following order: 60μm-30μm, 30μm-20μm, 20μm-10μm, and 10μm-5μm. After grinding, a highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates is obtained.

[0035] Example 2 is the same as Example 1, except that the silane coupling agent used in Example 2 is KH550.

[0036] Comparative Example 1 is the same as Example 1, except that KH560 was not added in Comparative Example 1.

[0037] Comparative Example 2 is the same as Example 1, except that no montmorillonite was added in Comparative Example 2.

[0038] Comparative Example 3 is the same as Example 1, except that no talc was added in Comparative Example 3.

[0039] Comparative Example 4 is the same as Example 1, except that calcium-based montmorillonite is used instead of sodium-based montmorillonite in Example 1. The calcium-based montmorillonite has the product code M813515, is montmorillonite K-10 calcium-based, and has a specific surface area of ​​240 m². 2 / g, purchased from Shanghai McLean Biochemical Technology Co., Ltd.

[0040] Comparative Example 5 is the same as Example 1, except that the conductive dispersion in Comparative Example 5 is prepared by the following method: Dispersant LD1126 was added to solvent NMP and stirred until homogeneous. Then, carbon nanotubes, Ketjen black, and graphene powder were added and stirred until homogeneous. The mixture was then transferred to a sand mill for sand milling. The sand milling process parameters were: rotation speed 2500 rpm, time 2 h, cooling circulating water temperature controlled below 10℃ during sand milling, and sand milling was stopped when the particle size of the dispersion was 1 μm to obtain a conductive dispersion. The mass percentages of dispersant LD1126, carbon nanotubes, Ketjen black, graphene powder, and carbon nanotubes in the conductive dispersion were 6%, 3%, 3%, and 4%, respectively.

[0041] Performance testing: Using a 50μm wire rod coating process, the coatings obtained in Example 1 and Comparative Examples 1-5 were uniformly coated onto both sides and edges of the titanium electrode. The titanium electrode was then dried in a high-temperature oven (130℃, 10 min). The resulting electrode had a protective coating thickness of 20μm.

[0042] The obtained protective coating was subjected to relevant performance tests, and the specific test results are shown in Table 1.

[0043] Pencil hardness: GB / T6739-1996.

[0044] Cross-cut adhesion test: GB / T 9286-2021.

[0045] Acidic salt spray test: GB / T 10125-2021, Acetic acid salt spray test.

[0046] Conductivity test: Four-probe tester.

[0047] Oxygen evolution performance: Three-electrode system (working electrode: electrodes obtained in Example 1 and Comparative Examples 1-5 respectively; counter electrode (graphite rod); reference electrode (Hg / HgO mercuric oxide reference electrode)); electrolyte is 1 mol / L KOH aqueous solution; voltage scan range is 0~1.8 V vs RHE; scan rate is 5 mV / s.

[0048] Table 1 , Based on the test data in Table 1, the reasons are analyzed as follows: In water electrolysis experiments, when using a bare titanium plate as the working electrode for oxygen production, a dense, insulating TiO2 passivation film instantly forms on the surface of the titanium electrode at the positive anodic potential. This film significantly hinders electron transfer, requiring an extremely high positive potential to break down the passivation layer and initiate oxygen evolution. However, when a highly conductive epoxy-modified coating is applied to the surface, a physical barrier is formed, preventing the electrolyte from directly contacting the titanium electrode and thus eliminating the anodic passivation reaction. Therefore, the oxygen evolution reaction can begin at a lower potential, with the oxygen evolution initiation potential shifted negatively by approximately 0.2V compared to the bare titanium plate. Similarly, the oxygen evolution overpotential is also reduced by approximately 0.2V.

[0049] Based on the adhesion data from Examples 1, 2 and Comparative Example 1, KH560 showed the best coupling effect with epoxy resin. Changing the type of coupling agent (KH550) or not adding a coupling agent would reduce the adhesion between the conductive epoxy coating and the titanium electrode plate, thereby reducing the coating's salt spray resistance life.

[0050] The data from Comparative Examples 2, 3, and 4 show that adding sodium montmorillonite and talc can effectively increase the service life of the coating. This is because after being compounded in the epoxy coating, the large-diameter talc and nano-sized montmorillonite can produce a synergistic barrier effect, reducing internal defects in the coating and forming a "nanomania," making the coating denser. This significantly improves the coating's salt spray resistance. Furthermore, during water electrolysis, the large amount of oxygen generated on the electrode surface impacts the coating. The synergistic barrier effect of sodium montmorillonite and talc prevents gas from entering, reducing the force exerted by the gas on the coating and thus increasing its service life. When only one of the two is used, either large-diameter talc or small-sized montmorillonite alone cannot effectively improve the coating's density. They will form uniform large or small defects on the coating surface, allowing gas to enter and damage the coating. In Comparative Example 4, sodium-based montmorillonite was replaced with calcium-based montmorillonite. Because sodium-based montmorillonite exhibits superior water absorption and swelling compared to calcium-based montmorillonite, it is more easily exfoliated into individual nanosheets, forming tortuous and longer penetration pathways within the epoxy coating, thus resulting in better barrier properties. In contrast, calcium-based sheets are difficult to exfoliate, tend to agglomerate into clumps, and exhibit a less pronounced maze effect. Therefore, sodium-based montmorillonite is more effective in improving the salt spray resistance life of the coating.

[0051] Based on the data from Example 1 and Comparative Example 5, changing the proportion of conductive filler and increasing the amount of carbon nanotubes to 4% slightly increases the conductivity of the coating. However, excessive addition of carbon nanotubes significantly affects the adhesion test results of the coating, reducing it from level 1 in Example 1 to level 5. This causes the salt spray resistance life of the coating to plummet to only 72 hours, severely impacting its actual performance.

[0052] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates, characterized in that, The coating has a particle size ≤5μm and comprises epoxy resin, latent epoxy curing agent, silane coupling agent, epoxy toughening agent, montmorillonite, talc, and conductive dispersion. The mass ratio of latent epoxy curing agent to epoxy resin, based on solids, is 1:(9-10). The total mass of latent epoxy curing agent and epoxy resin, based on solids, is denoted as epoxy resin matrix; The mass addition amount of silane coupling agent is 1-3% of the mass of epoxy resin matrix; The amount of epoxy toughening agent added is 7-10% of the mass of the epoxy resin matrix; The mass addition amount of montmorillonite is 1-3% of the mass of the epoxy resin matrix; The amount of talc added is 2-4% of the mass of the epoxy resin matrix; The mass addition of the conductive dispersion does not exceed 50% of the mass of the epoxy resin matrix, the solid content of the conductive dispersion is 15-17%, the conductive agent in the conductive dispersion is composed of Ketjen black, graphene and carbon nanotubes in a mass ratio of 4:4:2, and the particle size of the conductive dispersion is ≤1μm.

2. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The epoxy resin is E51 epoxy resin.

3. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The silane coupling agent is KH550 or KH560.

4. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, Montmorillonite is sodium-based montmorillonite.

5. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, Talc powder is in flake form.

6. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The graphene material, model number HG1004, was purchased from Henan Huage Graphene Materials Co., Ltd.

7. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The carbon nanotubes, model GP1001M, were purchased from LG Chem in South Korea.

8. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The Ketjen Black model is 600JD, purchased from Lion Corporation of Japan.

9. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The epoxy toughening agent, model number 9301, was purchased from Guangzhou Shanghe New Material Technology Co., Ltd.

10. The highly conductive and corrosion-resistant epoxy resin-based protective coating for titanium electrode plates according to claim 1, characterized in that, The latent curing agent, model HS-601 liquid latent curing agent, was purchased from Chuzhou Huisheng Electronic Materials Co., Ltd.